PENGUKURAN MORFOMETRI LONGSOR DI SUB DAS BOMPON MAGELANG JAWA TENGAH - Mahesa Ragil Syofyan; Fikri Haykal; febriandi febriandi (JURNAL GEOGRAFI, 2018)
This study aims to: 1) Know the morphometric characteristics of each type of avalanche in the Bompon sub-watershed 2) Find out the forms of conservation carried out on avalanches in the Bompon sub-watershed. Research carried out by means of field observations, therefore the data in this study are primary data where direct observations in the field. In general, data collection through three stages, namely field orientation, determining the location of observation and retrieval of data at a predetermined location. The results showed that generally the lands experiencing landslides were still lacking in conservation measures, then at the second point there were terraces, while land use was still used as mixed gardens except for the third landslide point intended for settlements with plant species such as trees teak, sengon, pineapple, bamboo, banana, cocoa and coffee, for this type of landslide, the average is rotational.